A po-ética do encontro humano: um estudo da biodanza como mediação da educação biocêntrica na transformação do emocionar para novas posturas éticas. - Dias, Amélzia Maria da Soledade (2013)
This research, organized with a clear perspective and a phenomenological approach, has as its investigative question: What ethics do Bio-dance participants promote through their lived experiences? Thus, it presents Bio-dance as a measure of Bio-centric Education, interfacing the theory and importance of these experiences in the lives of the participants in this system. Bio-dance is based on the bonding of human beings, as it is based on loving, co-existence through the ethics of diversity and re-linking with the Earth through the experience of belonging. This perspective makes clear that there is not necessarily any discontinuity between the social, the human and their biological bases. To live is to know and as living beings we are continuously our own reproducers in a network of interaction. The basic theory of Bio-dance is in Roland Toro, its creator. In Humberto Maturana we look for the basics about the biology of loving, in Edgar Morin knowledge is understood as a construction based on the theory of complexity and the basics of ethics, such as re-linking and with Emmanuel Levinas we search for an understanding of the ethics of diversity. These are the principal authors with whom we try to dialogue. The basis is in the interaction with persons involved in the research through the importance of their lived experience of Bio-dance. When Toro presents Bio-dance he proposes a system of development and growth of human potential organized by him around five lived-experience themes: Vitality, Sexuality, Creativity, Affectivity and Transcendence. For him, Bio-dance is a new sensitiveness regarding our existence, through the poetry of the human encounter where each one is invited to dance his/her own life, which unleashes new feelings. The practice of Bio-dance is a proposal for creating an environment for learning new ways of feeling, which in turn unleashes new ways of seeing and living life. Thus, there occurs a certain reflection regarding motivation, transformation and bonding in the dance of life . This leads to the following conclusion: the ethics brought to the fore by the experience of Bio-dance take place within new feelings, promote changes in how we act, creating a new life-style with significant transformation in the ways of living and co-existence with others in the manner in which we inhabit the Earth, having life as the center of all.